2018
DOI: 10.3390/min8080346
|View full text |Cite
|
Sign up to set email alerts
|

Metal Sequestration through Coupled Dissolution–Precipitation at the Brucite–Water Interface

Abstract: Abstract:The increasing release of potentially toxic metals from industrial processes can lead to highly elevated concentrations of these metals in soil, and ground-and surface-waters. Today, metal pollution is one of the most serious environmental problems and thus, the development of effective remediation strategies is of paramount importance. In this context, it is critical to understand how dissolved metals interact with mineral surfaces in soil-water environments. Here, we assessed the processes that gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 66 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Examination of polished embedded samples showed extensive infilling (clogging) of pores (Figure a) and passivation of larger brucite grains (e.g., ∼200 μm) that developed thick rinds (∼50 μm) of Mg-carbonate (Figure b). Surface passivation of reacting minerals by secondary precipitates may result from coupled dissolution–precipitation reactions, including brucite carbonation, that occurs at the mineral–fluid interface. ,, In addition, there is a volume increase when converting brucite (molar volume = 24 cm 3 /mol) to a Mg-carbonate mineral such as dypingite (404%). Harrison et al postulated that pervasive coatings on mineral surfaces and passivation of brucite grains by carbonate rinds (10–100s of microns) limit brucite carbonation.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of polished embedded samples showed extensive infilling (clogging) of pores (Figure a) and passivation of larger brucite grains (e.g., ∼200 μm) that developed thick rinds (∼50 μm) of Mg-carbonate (Figure b). Surface passivation of reacting minerals by secondary precipitates may result from coupled dissolution–precipitation reactions, including brucite carbonation, that occurs at the mineral–fluid interface. ,, In addition, there is a volume increase when converting brucite (molar volume = 24 cm 3 /mol) to a Mg-carbonate mineral such as dypingite (404%). Harrison et al postulated that pervasive coatings on mineral surfaces and passivation of brucite grains by carbonate rinds (10–100s of microns) limit brucite carbonation.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is not surprising considering that our system is heterogeneous due to the presence of minerals and HS. In fact, multiple studies have shown mineral nucleation and growth in under-saturated bulk solutions if organic materials and solid interfaces serve as nucleation templates to locally enrich ions (Deng et al, 2019;Hövelmann et al, 2018;Roberts et al, 2004). For example, Deng et al (2019) showed barite formation on organic films, despite their bulk solution was under-saturated with respect to barite, likely because of local super-saturation near the organic molecules.…”
Section: Secondary Mineralizationmentioning
confidence: 99%
“…47 Such interface-coupled dissolution-precipitation reactions have been previously described from AFM experiments 19 as well as larger scale hydrothermal experiments [48][49][50] and often with reference to potential environmental remediation, such as sequestration of atmospheric CO2 51,52 or removal of excess PO4 from eutrophic waters resulting from the overuse of phosphate fertilizers in agriculture, 53 as well as toxic element sequestration. [54][55][56] M-S-H, a Mg-silicate cement, is a practical environmentally friendly cement that furthermore could be highly suitable for the encapsulation of nuclear waste, 31,32 but whose development is limited by the need for cost-inefficient and limited silica fume. The new direct observations presented here, which show the formation of Mg-silicates as a result of the dissolution of widely available quartz (in the form of sand) at ambient temperatures, may therefore be fundamental knowledge leading to the production of Mg-silicate cement.…”
Section: Implications For the Environmentmentioning
confidence: 99%